2019
DOI: 10.18517/ijaseit.9.4.9461
|View full text |Cite
|
Sign up to set email alerts
|

Improving Thermal Performance of Dwelling Single Glass Windows Using Secondary Glazing in the UK

Abstract: In the globe, 40% of heat losses in domestic buildings were caused by single glazing windows usage and around 20% were due to air infiltration. Therefore, an improvement for the single glazed windows and reducing the air infiltration must be considered to lower the energy consumption. This study aims to investigate the thermal performance of the secondary glazing sheet on the ordinary windows in the low-income dwellers. The PVC sheets were used as the secondary glazing which easies to tailor and fit into the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
1
2
0
2
Order By: Relevance
“…In line with the findings of the studies on the thermal insulation properties of secondary glazed windows, open-ended answers provided by some respondents in our study suggest better indoor thermal stability and a reduced demand for heating and cooling (Kim and Felkner, 2018; Fitton et al , 2017; Harjunowibowo et al , 2019; Smith et al , 2012). One of the respondents commented on this with the following:Both heating and cooling times have been reduced.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In line with the findings of the studies on the thermal insulation properties of secondary glazed windows, open-ended answers provided by some respondents in our study suggest better indoor thermal stability and a reduced demand for heating and cooling (Kim and Felkner, 2018; Fitton et al , 2017; Harjunowibowo et al , 2019; Smith et al , 2012). One of the respondents commented on this with the following:Both heating and cooling times have been reduced.…”
Section: Resultssupporting
confidence: 88%
“…Reporting on simulations for different secondary glazed windows in four different locations in New Zealand, Smith et al,, (2012) and Smith & Isaacs, (2009) found that secondary glazing can improve, compared to single glazing, the R-value of a window from 130% through to 290%, depending on the glazing and materials used. An experimental study from the United Kingdom (UK), showed that an eco-friendly PVC sheet could reduce the thermal transmittance of old single glazing windows by up to 57% and provide a higher and more stable indoor air temperature (Harjunowibowo et al 2019).…”
mentioning
confidence: 99%
“…Bahkan penggunaan material polikarbonat pada dinding dan atap mampu menghemat hingga 60% (Harjunowibowo et al, 2017). Hal ini sejalan dengan penelitian Harjunowibowo et al (Harjunowibowo et al, 2019) bahwa hilang panas pada bangunan disebabkan oleh penggunaan kaca seperti di rumah kaca sebesar 40%. Lebih jauh, dalam penelitian tersebut dikatakan bahwa penggantian kaca tunggal menjadi kaca ganda dengan plastic polyvinyl chloride (PVC) mampu meningkatkan nilai thermal resistant-nya (u-value) hingga hampir 60%.…”
Section: Pendahuluanunclassified
“…The measurements were repeated ten times to calculate the statistics of the results. The wavelength was measured by calculating the mean value λ and the uncertainty ∆λ used Standard Error followed the equations ( 4) and ( 5) [21,22]…”
Section: Calibrationmentioning
confidence: 99%